Tinjauan E-Learning Untuk Teknologi Energi Baru Terbarukan Di Pendidikan Tinggi Indonesia - Dwi Otik Kurniawati; Taufiq - Kamal; Ahmad Ghuril Muhajjalin (Universitas Islam Lamongan, 2020)
Information technology is very environmentally friendly. As a result, the use of e-learning platforms as a medium in renewable energy education is a creative method to empower teaching for students and researchers to take action for sustainable development. This article provides a comparison of several existing e-learning platforms for energy education learning media.E-learning platforms such as Energy University and Power Energy Lab E-learning and others are presented and qualitative comparisons between platforms are made. Generally, they use dynamic websites which are developed manually or they use a Content Management System. They provide a variety of teaching materials, although, there are other, more effective and tailored ways to learn in a distance learning environment. This article also highlights a vision of an applied e-learning platform, based on a study on renewable energy in Indonesia. In this context, a detailed selection is made among the various open source platforms to select the one that best fits the training environment and vision. As a result, choices were made on the Moodle platform